Outcome Prospective of Late Duodenal Perforation Repairs in Elderly - Sajid Anwer, Muhammad Nauman Ashraf, Imtiaz Ahmed Khattak, Yasir Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Perforated duodenal ulcer is the communal emergency seen in surgical department, and postoperative complications of this emergency surgeries are very high which requires the related factors identification with this incidence. Aim: This study was designed to evaluate duodenal ulcer in older patients by revealing the patient's health status, early and late repair, choice of surgical procedure, and differences between older and younger duodenal ulcer patients. Study Design: A Retrospective study. Place and duration: In the Surgical Unit 2 of, Sheikh Zayed Medical College/ Hospital Rahim Yar Khan for two-year duration from January 2020 to December 2021. Methods: This study included 140 patients were alienated into 2 age groups as geriatric patients’ group (A) and adult age group (B). Patient age, gender, co-morbidities, drug use, presence of Helicobacter pylori infection, medical conditions that may have been affected by perforation, such as characteristic pain (severe upper abdominal pain or vague abdominal pain), extent of symptoms at presentation, smoking, outcomes of late repair versus early repair was recorded. Results: 140 patients were registered in the analysis. Group I (n = 70) consisted of geriatric patients (age> 65) and Group-II (n = 70) adults’ patients (age <65). Both groups have male dominance in this study. In both groups, the most common comorbidities were diabetes (25.7% and 8.6%, respectively) and arterial hypertension (42.8% and 41.4%, respectively), hypertension (p = 0.002) and coronary artery disease (p = 0.035) was much high in group I, while morbidity and mortality were higher in the group of elderly patients. Conclusion: Duodenal perforation is a serious disease that requires urgent surgical intervention, especially in the geriatric age. Keywords: Duodenal ulcer perforation, acute abdomen, geriatric surgery.